SIGNIFICANCE OF CROSSBORDER/TRANSNATIONAL COOPERATION PROGRAMS FOR ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT - Bekić, Bojana; Puškarić, Anton; Ivanović, Lana (Economics of Agriculture, 2011)
Programs of crossborder/transnational cooperation represent an instrument of the European union which should contribute to establishing of new and strengthening of already existing connections between different institutions in Republic of Serbia and the surrounding countries. In the paper is given the overwiev of programs through which Serbia can establish crossborder i.e. transnational cooperation with neigborouing countries that is EU member countries. Also, authors gave the list of projects financed within South East Europe Transational Cooperation Program – SEE Program, from the beginning of the Program till today, with especial accent on projects in in the feld of innovation and enterprenuership. At the example of TECH.FOOD Project, which is one of many projects that support development of enterprenuership and which are fnanced within SEE Program, authors present functioning of project partnership and main goals of the Project.